Aluminium-26 grain boundary diffusion in pure and Y-doped polycrystalline α-alumina. (1st April 2017) - Fielitz, Peter; Kelm, Klemens; Bertram, Rainer; Chokshi, Atul H.; Borchardt, Günter
Abstract: Aluminium grain boundary diffusivities were measured in pure and Y-doped polycrystalline α-Al2 O3 using the artificial aluminium isotope 26 Al as a tracer. An advanced preparation technique for the 26 Al tracer source enabled secondary ion mass spectrometry (SIMS) measurements to analyse the 26 Al depth distributions in the polycrystalline materials. Simultaneously performed 18 O and 26 Al tracer diffusion experiments demonstrated clearly in the most direct way that 26 Al grain boundary diffusion is significantly faster than 18 O grain boundary diffusion. There was no significant difference in aluminium grain boundary diffusivities in pure and Y-doped polycrystalline α-Al2 O3 . The experimental results of this work imply that diffusion creep in alumina is unlikely to be controlled by Al grain boundary diffusion. Graphical abstract: Simultaneously performed 18 O and 26 Al tracer diffusion experiment. Image